Advances and backdrops of teacher training courses in natural sciences area (Research, Society and Development, 2021)
Educational public policies related to initial teacher training assumed a centrality in the field that concerns educational research. We analyzed the Pedagogical Projects of Courses (PPC) aiming to identify advances and setbacks in teacher training in Biological Sciences, in Chemistry, and in Physics at the Universidade Federal de Santa Maria, campus from Santa Maria/RS, in relation to the National Curriculum Guidelines for teacher training. We carried out a qualitative, documentary, and descriptive research using content analysis as analysis methodology. From the results found, we realized that the Internship, Practice as a Curriculum Component, Complementary Activity and Total Credit Hours of the courses are, for the most part, in line with the laws that guide CNE/CP Resolutions N. 01/2002, 02/2002 and 02/2015. However, the courses are out of step with the BNC-Training guided by Resolution CNE/CP N. 02/2019. Thus, we infer that encouraging the development of a better and diversified PPC may lead to teacher training towards the expected profile.